Long non‐coding RNA LINC00665 promotes melanoma cell growth and migration via regulating the miR‐224‐5p/VMA21 axis. Issue 1 (12th December 2020) - Wang, Xiaonan; Wang, Yanbing; Lin, Feifei; Xu, Meng; Zhao, Xin
Abstract: Melanoma is an aggressive malignant skin tumor endangering the health of patients. Long non‐coding RNAs (lncRNAs) and microRNAs (miRNAs) have been increasingly reported to be implicated in the carcinogenesis of melanoma. Long intergenic non‐coding RNA 00665 (LINC00665) has been found to exert important regulatory roles in some cancers, yet its function in melanoma remains to be investigated. QRT‐PCR analysis was conducted to evaluate the relative expression of RNAs. Functional experiments in vitro including colony formation, EdU, wound‐healing and transwell assays, as well as in vivo xenograft assays, were utilized to study the role of LINC00665 in melanoma. Mechanical experiments were implemented to probe into the molecular linkage of LINC00665, miR‐224‐5p and VMA21. LINC00665 was abnormally highly expressed in melanoma cells. Silencing LINC00665 could inhibit the proliferation and migration of melanoma cells. LINC00665 sponged miR‐224‐5p to upregulate VMA21. VMA21 knockdown exerted similarly interfering effects on above biological processes in melanoma cells. However, VMA21 overexpression abolished the in vitro and in vivo outcomes of LINC00665 silencing. LINC00665 promotes proliferative and migrating abilities of melanoma cells via targeting miR‐224‐5p/VMA21 axis.